KASTA PADA PERKAWINAN ORANG HINDU DI KAMPUNG MADRAS - Utami, Novita Indah; Syahminan, Mhd.; Muary, Rholand (SEMAR : Jurnal Sosial dan Pengabdian Masyarakat, 2024)
This research aims to determine the existence of inter-caste marriages based on Hindu religious rules, the factors causing the occurrence of inter-caste marriages in Madrash Village, and the implications of inter-caste marriages from a legal, socio-cultural and religious perspective in Madrash Village, Medan City. The data in this research were collected using methods, namely 1) observation, 2) interviews, 3) recording, 4) literature. This research was conducted in the Banjar Brahmana Bukit community, Bangli Regency and Bangli Regency. The subjects of this research are 1) those who marry from different castes, 2) community leaders 3) sub-district leaders, 4) religious leaders in Banjar Brahmana Bukit, 5) Banjar Brahmana Bukit Youth Organization, 6) The community itself is based on purpose. The results of the research show that: 1) the existence of inter-caste marriages in Madrash Village still exists. However, if it is related to Hindu law based on the Manawa Dharmasastra Book, it is recommended that marriages be carried out between people of the same caste because marriages with different castes will affect offspring or the birth of babies. 2). People who marry from different castes in Madrash Village are generally caused by two factors, namely internal factors which refer to personal feelings and love and external factors refer to the environment where a good or bad environment will influence a person's character and personality. 3) the implications of inter-caste marriage in Madrash Village from a legal perspective, basically everyone has the same rights, obligations and the same position from a legal perspective. However, according to social culture and religion, there are restrictions for those who enter into marriages between different castes based on the traditions and traditions of the community itself.